Multimorbidity clusters in adults 50 years or older with and without a history of cancer: National Health Interview Survey, 2018 - Gabriela Plasencia; Simone C. Gray; Ingrid J. Hall; Judith Lee Smith (BMC Geriatrics, 2024)
Abstract Background Multimorbidity is increasing among adults in the United States. Yet limited research has examined multimorbidity clusters in persons aged 50 years and older with and without a history of cancer. An increased understanding of multimorbidity clusters may improve the cancer survivorship experience for survivors with multimorbidity. Methods We identified 7580 adults aged 50 years and older with 2 or more diseases—including 811 adults with a history of primary breast, colorectal, cervical, prostate, or lung cancer—from the 2018 National Health Interview Survey. Exploratory factor analysis identified clusters of multimorbidity among cancer survivors and individuals without a history of cancer (controls). Frequency tables and chi-square tests were performed to determine overall differences in sociodemographic characteristics, health-related characteristics, and multimorbidity between groups. Results Cancer survivors reported a higher prevalence of having 4 or more diseases compared to controls (57% and 38%, respectively). Our analysis identified 6 clusters for cancer survivors and 4 clusters for controls. Three clusters (pulmonary, cardiac, and liver) included the same diseases for cancer survivors and controls. Conclusions Diseases clustered differently across adults ≥ 50 years of age with and without a history of cancer. Findings from this study may be used to inform clinical care, increase the development and dissemination of multilevel public health interventions, escalate system improvements, and initiate innovative policy reform.